2020
DOI: 10.1080/03323315.2020.1734044
|View full text |Cite
|
Sign up to set email alerts
|

The care ceiling in higher education

Abstract: Mostly not-employed mothers set the cultural standards for 'good' parenthood and 'good' education, while childless subjects set the standards in the world of work; [those] … want to do both, will be measured by the standards set by those … that are only into one of the spheres (Bomert and Leinfellner, 2017:118, citing König, 2012: 193) Lynch, Ivancheva, O'Flynn, Keating and O'Connor 2020 Care Ceiling in Higher Education -Irish Educational Studies (pre-publication version) 2relations more generally, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…It also involved research with those who were cared for as well as carers. The studies were qualitative: over 200 conversations and interviews were held with people from different social class, age, gender and ethnic backgrounds, and in different care and professional settings; focus groups, site visits and observations within organizations and households were undertaken, while documentary evidence was also compiled (Ivancheva et al, 2019;Lynch et al, 2009bLynch et al, , 2012Lynch et al, , 2020. 2 What is clear from these studies is that the nurturing work that produces love, care and solidarity is identified by those doing and receiving it as a distinct set of social relations that have a formative impact and are deeply normative in character.…”
Section: Introductionmentioning
confidence: 99%
“…It also involved research with those who were cared for as well as carers. The studies were qualitative: over 200 conversations and interviews were held with people from different social class, age, gender and ethnic backgrounds, and in different care and professional settings; focus groups, site visits and observations within organizations and households were undertaken, while documentary evidence was also compiled (Ivancheva et al, 2019;Lynch et al, 2009bLynch et al, , 2012Lynch et al, , 2020. 2 What is clear from these studies is that the nurturing work that produces love, care and solidarity is identified by those doing and receiving it as a distinct set of social relations that have a formative impact and are deeply normative in character.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, Dorie described a sense of urgency around creating a more reliable structure for students as well as her of paraprofessionals as soon as possible, explaining: "I'm trying to figure out the structure and schedule that will work for everyone." Dorie's experiences at home were also representative of other teachers in our sample insofar as heterosexual couples with children in which both spouses worked during the shutdown tended to rely disproportionately on mothers to provide childcare, mirroring the experiences of mothers across the United States and other parts of the Global North (Calarco et al, 2021;Lynch et al, 2020). Dorie's description of her husband having a full-time job and being "very busy right now" could be seen as applying equally, if not more, to her own circumstance.…”
Section: Caring For Selfmentioning
confidence: 88%
“…Within institutions such as schools, as well as other noneducational organizations, scholars have long noted that care work is frequently uncompensated and left to females (Lynch et al, 2020). In fact, some conceptualizations of care work in schools are themselves rooted in normative notions of femininity.…”
Section: Care Work Teaching and Gendermentioning
confidence: 99%
“…However, there is danger in focusing on 'an image of academic development as precarious and liminal [as opposed to] powerful' (Roxå and Mårtensson 2017). Career conditions must be considered within a broader picture of working conditions in Irish Higher Education where 'idealised care-free worker model operates as a care ceiling over women particularly' (Lynch et al 2020) where racism and sexism persist (Kempny and Michael 2021;MacNeela et al 2022) and which people navigate by many intersectionalities that mark them as not of the ideal.…”
Section: P O S T P R I N Tmentioning
confidence: 99%